Introductory repetition in the poetry Marouf Al-Rusafi - حيدر علي; محمد حسن عماد الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The poetry of revival is replete with many stylistic phenomena , which made it a milestone in the history of Arabic poetry and a point towards change and renewal in the content and content of poetry , and these phenomena have varied from one poet to another according to its own approach , philosophy , which in turn reflected a style of its own , but certain phenomena won the consensus of many poets of revival phase , especially the phenomenon of introductory repetition that reflected a set of signs that the poet tried to communicate . In this research , work is being done to investigate this phenomenon , and to explore its dimensions and implications , also to know the added value which it provided to the Arab poetry in general , and poetry of revival in particular .